Pengaruh Suplementasi Lisin terhadap Karakteristik Karkas Itik Lokal Jantan Umur Sepuluh Minggu - Amiruddin, Bahtiar Nur Khalis; Sudiyono, Sudiyono; Ratriyanto, Adi (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2011)
The objective of the study was to determine the effect of lysine supplementation in ration on carcass yield, abdominal fat and fat content of ten-week old male local duck meat. The study used 80 male local ducks aged two weeks (average weight 326.40±31.84 g). The experimental design used was Completely Randomized Design with four treatments, consisted of four replications with five male local ducks each. Rations consisted of pollard, yellow corn, soybean meal, palm oil, premix and lysine (in the form of L-Lysine HCl). The basal diet was supplemented with lysine at the amount of 0 (control), 0.05, 0.10 and 0.15%. The variables observed were the slaughter weight, abdominal fat percentage, carcass yield and fat content of the meat. The results showed that lysine supplementation in the diet of local duck ten-week old male decreased (P<0.01) abdominal fat but did not affect slaughter weight, carcass yield and fat content of meat. It can be concluded that lysine supplementation of 0.15 percent of the total ration can reduce abdominal fat percentage of ten-week old male local duck meat.